Modeling of finite-size droplets and particles in multiphase flows - Khare, Prashant; Wang, Shanwu; Yang, Vigor (Chinese journal of aeronautics, 2015)
The conventional point-particle approach for treating the dispersed phase in a continuous flowfield is extended by taking into account the effect of finite particle size, using a Gaussian interpolation from Lagrangian points to the Eulerian field.The inter-phase exchange terms in the conservation equations are distributed over the volume encompassing the particle size, as opposed to the Dirac delta function generally used in the point-particle approach.The proposed approach is benchmarked against three different flow configurations in a numerical framework based on large eddy simulation（LES） turbulence closure.First, the flow over a circular cylinder is simulated for a Reynolds number of 3900 at 1 atm pressure.Results show good agreement with experimental data for the mean streamwise velocity and the vortex shedding frequency in the wake region.The calculated flowfield exhibits correct physics, which the conventional point-particle approach fails to capture.The second case deals with diesel jet injection in quiescent environment over a pressure range of 1.1–5.0 MPa.The calculated jet penetration depth closely matches measurements.It decreases with increasing chamber pressure, due to enhanced drag force in a denser fluid environment.Finally, water and acetone jet injection normal to air crossflow is studied at1 atm.The calculated jet penetration and Sauter mean diameter of liquid droplets compare very well with measurements.